1982
DOI: 10.1111/j.1524-4725.1982.tb01119.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgery of Extensive, Subclinical Lentigo Maligna

Abstract: Because atypical melanocytes in some cases of lentigo maligna extend beyond the standard 5‐mm margins of nonpigmented, normal‐appearing skin, surgical removal of these lesions with histologic control is advocated. Two case reports are described and illustrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Recurrence after destructive modalities is due in large part to microscopic extension of LM, which has been reported as much as 1.5–3 cm beyond the clinical margin 33–35 . Among our 45 patients, the lesions extended microscopically an average of 13 mm beyond the clinically evident tumor, thereby making a final wound size that averaged 25 × 28 mm larger than the clinical lesion.…”
Section: Discussionmentioning
confidence: 75%
“…Recurrence after destructive modalities is due in large part to microscopic extension of LM, which has been reported as much as 1.5–3 cm beyond the clinical margin 33–35 . Among our 45 patients, the lesions extended microscopically an average of 13 mm beyond the clinically evident tumor, thereby making a final wound size that averaged 25 × 28 mm larger than the clinical lesion.…”
Section: Discussionmentioning
confidence: 75%
“…6,15,25,[33][34][35]38,40,48 Mounting evidence supports the concept that while margins for trunk and extremity invasive melanoma may be narrowed without reducing survival, 9,18,19 MIS, especially on the head and neck, may need even wider margins than previously thought. 6,15,25,[33][34][35]38,40,48,56 In a series of 200 melanomas, Zitelli et al 32 found that the subclinical extension of melanoma measured 6 mm or less in 80% of patients but reached 1.5 cm in a significant number, especially in thinner lesions. Breuninger et al 25 systematically examined patterns of horizontal spread of melanoma by performing 10m step sections through the entire peripheral margin of 54 MM, including 10 lentigo maligna melanomas (LMMs).…”
Section: Case Report and Discussionmentioning
confidence: 99%
“…Furthermore, melanomas may arise in precursor lesions of lentigo maligna, 3 which resemble pigmentary changes of sun-damaged skin. Melanomas in sun-damaged skin are often amelanotic 4 at the periphery, potentially hiding areas that would exhibit histologic nesting and invasion. These characteristics of indistinct margins are much less likely on the trunk or proximal extremities, and therefore, complete excision is more common, resulting in lower recurrence rates in these sites.…”
mentioning
confidence: 99%